First-line chemotherapy with raltitrexed in metastatic colorectal cancer: an Association des Gastro-entérologues Oncologues (AGEO) multicentre study. Issue 5 (May 2022) - Gallois, Claire; Hafliger, Emilie; Auclin, Edouard; Perret, Audrey; Coutzac, Clélia; Turpin, Anthony; Pellat, Anna; Randrian, Violaine; Basile, Debora; Faroux, Roger; Pernot, Simon; Locher, Christophe; et al.
Abstract: Background: In case of contraindication or intolerance to fluoropyrimidines, raltitrexed is a validated alternative in metastatic colorectal cancer (mCRC), associated or not with oxaliplatin. Little is known about the outcomes of raltitrexed combined with irinotecan or targeted therapies. Methods: This retrospective multicentre study enroled mCRC patients treated with first-line raltitrexed-based chemotherapy. Treatment-related toxicities were recorded. Progression-free survival (PFS) and overall survival (OS) were calculated from treatment start. Results: 75 patients were treated with raltitrexed alone, TOMOX, or TOMIRI with or without bevacizumab. Grade 3–4 adverse events were seen in 31% of patients, without significant difference between the different treatment schedules. amongst the 36 patients with a history of fluoropyrimidine-induced cardiac toxicity, none developed cardiovascular events on raltitrexed. Median PFS and OS were 10.6 (95% CI 8.2 – 13.1) and 27.4 months (95% CI 24.1–38.1), respectively. Considering the chemotherapy regimen, TOMOX was significantly associated with better PFS and OS compared to TOMIRI and raltitrexed alone. Conclusions: In patients with mCRC not eligible for fluoropyrimidines, first-line raltitrexed-based chemotherapy had an acceptable safety profile. PFS and OS were consistent with usual survival data in mCRC, and significantly better in patients treated with TOMOX, independently of associated targeted therapies.